Spherical projectile impact using compressed air for frequency response function measurements in vibration tests. (1st December 2019) - Hosoya, Naoki; Kato, Junya; Kajiwara, Itsuro
Graphical abstract: Highlights: Establishment of a spherical projectile impact excitation system using compressed air. Verification of the repeatability and the frequency component of the generated impulse excitation force. Control of the frequency component and the amplitude included in an excitation force. Demonstration of pseudo-non-contact and non-destructive frequency response function measurements. Abstract: We conduct vibration tests using the excitation force generated by the impact of a spherical projectile on the excitation point of the target structure produced by compressed air to obtain a pseudo-non-contact (a non-constraint) and non-destructive frequency response function (FRF) measurement. In general, obtaining the dynamic properties of a target structure requires inputs by a contact device such as an impulse hammer or a vibrator and subsequent measurements of the responses using an accelerometer or a laser Doppler vibrometer. Then the FRFs are estimated from the input–output relationship. However, if a target structure is a rotating structure such as a wind turbine, generating a vibration using a contact device is challenging because those wired devices are at risk caught in the structure. This method can control frequency components and amplitudes in the excitation force by changing a material and a size of the spherical body, because the force is determined by a radius, Young's modulus and Poisson's ratio of the spherical body. In addition, the specifications of the spherical projectile device such as an O-ring, a volume of the cylinder, a barrel length, etc. adjust, the impact velocity can be given. This method yields a highly reproducible excitation force, realizing input-detection-free FRF measurements, which we formulated to obtain FRFs by response measurements alone in the frequency range where the amplitude of the Fourier spectra of the excitation force is considered constant. As a result of using a load cell to assess the excitation force generated by a spherical projectile device, we conclude that the vibratable frequency bandwidth is up to about 20 kHz. Additionally, a comparison of the FRFs of an aluminum block using the proposed method and finite element analysis validates this method.